Mitigating Pollution at the Source and Textile Waste Minimization in Poland: Findings from In-House Research - SKURPEL, Dagmara (Journal of Environmental Management and Tourism, 2023)
Currently, since the fast fashion phenomenon has existed, the number of new collections appearing in chains and online stores has increased from four to about fifty per year, thus the amount of clothing bought by one person per year is on average 16 kilograms, and as a result, the amount of clothing thrown away by Poles themselves is approximately 2.5 million tons of waste per year. From 1996 to 2012, the amount of clothing purchased per capita increased globally by 40%. In the years 2000–2014 it was 60% more. The problem needs to be solved because it causes a lot of damage to the environment and pollutes the environment a lot. All we need to do is extend the life cycle of clothes by 10% and we will save as much as three million tons of CO2 and 150 million liters of water per year. The aim of the article is to analyze two closely related areas: customers' awareness of the impact of clothing production on the environment and their attitude towards reusing unwanted clothing, and solutions implemented by e-shops in the fashion industry in the area of consumer returns management. The analysis used the results of secondary research and the author's own periodic research from 2017-2023.